A vocação profética em Atos dos Apóstolos: uma análise exegética de atos 2 e 9 - Stephen, Daniel Neves (2023)
Prophecy was an institution of great relevance to Judaism and, consequently, also had a great influence on the movement of Jesus and the first Christian communities. One of the essential aspects of prophetism are the reports of prophetic vocation, which indicate the beginning of the prophet's activity. In view of this, this research has as its object the prophetic vocation in Acts of the Apostles, where Luke narrates the beginning of the missionary activity of the disciples of Jesus through an experience characterized by the prophetic vocation. There are two texts that will be analyzed in the research: Acts 2:1-41 which narrates the experience of the first disciples and Peter at Pentecost and Acts 9:1-19a which tells the experience of Paul on the road to Damascus. The objective is to understand in an exegetical way these biblical texts that point to a prophetic vocation in the Lucan perspective. The relevance of this research is due to the important collaboration that Acts of the Apostles offers for ecclesiology by punctuating the continuity of the mission through the prophetic vocation in the primitive community of disciples. For this, bibliographical research will be used as a methodology, at first, whose purpose will be to understand the book of Acts in a introductory way and soon after the origin and development of the prophetic vocation that arises in Judaism and is presented in primitive Christianity with Luke. Later a historical-critical exegetical analysis of the passages of Acts 2.1-41 and 9.1-19a with the intention of identifying the guiding elements that legitimize the prophetic vocation in Luke. Therefore, it is expected to understand the importance that the prophetic vocation story had for the primitive communities that were heirs and continuers of the mission of Jesus.(AU)